Exogenous colonization of carbapenem-resistant Klebsiella pneumoniae and vancomycin-resistant Enterococcus in preterm infants: a PFGE-based molecular epidemiology study - Aktaş, Ahmet; Tanriverdi, Elif Seren; Demirkalp, Tuba; Otlu, Barış; Nakipoğlu, Yaşar (The Journal of Infection in Developing Countries, 2026)
Introduction: Carbapenem-resistant Klebsiella pneumoniae (CRKP) and vancomycin-resistant Enterococcus (VRE) pose significant threats in neonatal intensive care units (NICUs) due to their high transmission potential and limited treatment options. Identifying the source of colonization and detection of predominant antibiotic-resistant genes are crucial for effective infection control measures. Methodology: In this study, we analyzed 20 carbapenem-susceptible Klebsiella pneumoniae (CSKP) and 20 Vancomycin-susceptible Enterococcus (VSE) of meconium versus 20 CRKP and 20 VRE of rectal swabs isolates, respectively, from 20 preterm infants hospitalized in the NICU. Pulsed-field gel electrophoresis (PFGE) and arbitrarily primed PCR (AP-PCR) were used for molecular epidemiological analysis. The presence of carbapenemase (blaOXA-48, blaNDM, blaKPC) and Vancomycin-resistance (vanA, vanB, vanC) genes was investigated by multiplex PCR. Results: No predominant outbreak strain was detected, and isolates exhibited high genetic diversity, indicating an exogenous source of colonization of both CRKP and VRE. PFGE analysis revealed 24 distinct genotypes among CRKP and 25 among VRE isolates, with a clustering rate of 57.5%. The most commonly detected resistance gene in CRKP isolates was blaOXA-48 (50%), followed by blaNDM (35%) and blaKPC (10%). Among VRE isolates, only the vanA gene was present (85%). Conclusions: The absence of a clonal outbreak and the detection of resistance genes primarily on plasmids indicate healthcare-associated transmission rather than endogenous selection. This highlights the critical role of hand hygiene and strict infection control measures in preventing multidrug-resistant pathogen colonization in vulnerable preterm infants.